The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.4238/2013.december.13.2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of CCND1 and PTEN in progression of esophageal squamous carcinoma

Abstract: ABSTRACT. Cyclin D1 (CCND1) plays a significant role in G1-S transition of cell cycle, and phosphatase and a tensin homologue (PTEN) negatively regulate cell cycle through phosphatidylinositol 3-kinase (PI3K)/AKT signaling. CCND1 and PTEN genetic polymorphisms might induce susceptibility to the occurrence of esophageal squamous cell carcinoma (ESCC). Three hundred and four ESCC patients and 413 healthy controls from Anyang, China, were enrolled in this study. All genotyping at CCND1 (807 G/A) and PTEN (rs70184… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…Xu et al [8] revealed that the carriers of homozygous mutant of rs701848 polymorphism increased ESCC risk than those with wild-type homozygotes. It is worthy to note that in another 2 case-control studies, one observed that the distribution of genotypes or alleles at PTEN rs701848 T/C possessing notably higher proportion in ESCC cases (n=304) than in the controls (n=413) [6], however, the other study did not found any significant differences of the genotype in PTEN rs701848 in ESCC patients (n=226) [18]. Although above studies investigated the cancer patients, the different kind of cancer and populations could differ in genetic variations, which can contribute to the discrepancies in these results.…”
Section: Discussionmentioning
confidence: 99%
“…Xu et al [8] revealed that the carriers of homozygous mutant of rs701848 polymorphism increased ESCC risk than those with wild-type homozygotes. It is worthy to note that in another 2 case-control studies, one observed that the distribution of genotypes or alleles at PTEN rs701848 T/C possessing notably higher proportion in ESCC cases (n=304) than in the controls (n=413) [6], however, the other study did not found any significant differences of the genotype in PTEN rs701848 in ESCC patients (n=226) [18]. Although above studies investigated the cancer patients, the different kind of cancer and populations could differ in genetic variations, which can contribute to the discrepancies in these results.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, rs701848 is located in untranslated regions (UTR) variant 3 prime, which targeted by Micro-Ribonucleic-Acid (miRNA) might alter the strength of miRNA binding, with consequence on regulation of target genes, thereby affecting the individuals' cancer risk. [23][24][25] Jang et al 26 indicated that the polymorphisms of PTEN rs701848 T/C and rs2735343 C/G might represent crucial modifying factors for development of ESCC in a Chinese casecontrol study. Some studies 27,28 indicated that PTEN hypermethylation is present in ESCC and PTEN methylation status may represent a valuable biomarker for ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information extracted from the included publications is provided in Table 1 . Of the 23 included studies, there were ten groups of Caucasians, 21 23 , 25 , 28 , 31 , 32 , 34 , 38 , 43 ten groups of Asians, 21 , 26 , 27 , 29 , 35 – 37 , 39 – 42 and three groups of mixed ethnicities. 24 , 30 , 33 Among the 23 included studies, the classic polymerase chain reaction-restriction fragment length polymorphism assay was the most frequently used method to genotype the CCND1 G870A polymorphism.…”
Section: Resultsmentioning
confidence: 99%